2010
DOI: 10.1111/j.1540-6261.2009.01528.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Hot Hands Exist among Hedge Fund Managers? An Empirical Evaluation

Abstract: We examine whether hot hands exist among hedge fund managers. In measuring performance, we use hedge fund style benchmarks. This allows us to control for optionlike features inherent in returns from hedge fund strategies. We take into account the possibility that reported asset values may be based on stale prices. We develop a statistical model that relates a hedge fund's performance to its decision to liquidate or close in order to infer the performance of a hedge fund that left the database. While we find si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
123
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(132 citation statements)
references
References 45 publications
8
123
0
1
Order By: Relevance
“…5 Our third key finding is that the flow-return cycle contributes significantly to the observed performance persistence in hedge funds. Agarwal and Naik (2000); Kosowski, Naik, and Teo (2007); and Jagannathan, Malakhov, and Novikov (2010), to mention only a few, documented persistence in hedge fund performance. In theory, our finding of a positive contemporaneous relation between flows and returns could be caused by a combination of performance-chasing flows and some type of fundamental momentum in hedge fund returns.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Our third key finding is that the flow-return cycle contributes significantly to the observed performance persistence in hedge funds. Agarwal and Naik (2000); Kosowski, Naik, and Teo (2007); and Jagannathan, Malakhov, and Novikov (2010), to mention only a few, documented persistence in hedge fund performance. In theory, our finding of a positive contemporaneous relation between flows and returns could be caused by a combination of performance-chasing flows and some type of fundamental momentum in hedge fund returns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The existence of the flow-return cycle raises the question of whether flows have a role in the observed persistence in hedge fund performance. For example, Agarwal and Naik (2000), Kosowski et al (2007), and Jagannathan et al (2010) found that hedge fund returns exhibit momentum: Past winning funds tend to outperform past losing funds. The link between the flow-return cycle and momentum was investigated in the context of mutual funds by Lou (2012), who found that mutual fund flow-based return predictability can fully account for the persistence in mutual fund performance and partially account for stock price momentum.…”
Section: Relation To Performance Persistencementioning
confidence: 99%
“…Although we would expect investors to respond negatively to such a delay, a poorly performing hedge fund may still benefit, on the margin, by delaying the disclosure of its performance. For instance, the model of delayed disclosures by Acharya, DeMarzo, and Kremer (2011) would suggest that as long as there is a sufficient probability that delays are being caused by nonstrategic rather than 6 See, for example, Kosowski, Naik, and Teo (2007), Boyson (2008), Fung, Hsieh, Naik, andRamadorai (2008), and Jagannathan, Malakhov, and Novikov (2010). Prior studies also find a relation between hedge fund performance and systematic risk (Bali, Brown, and Caglayan (2011).…”
Section: Hypotheses and Empirical Predictionsmentioning
confidence: 99%
“…* and ** indicate significance at the 5% and 1% levels, respectively. related to share restrictions (Aragon (2007)) and past performance (Boyson (2008), Jagannathan et al (2010)). Overall, the evidence confirms our earlier analysis of portfolio returns and shows that the predictability we document is separate from other known predictors of fund performance.…”
Section: Figure 3 Monthly Style-adjusted Returns Of Portfolios Trackimentioning
confidence: 99%
“…In response, I observe the old marketing adage 'price is only relevant in the absence of value', and suggest that this rule applies just as much to hedge funds as it does to any other good or service. There have existed in the past and continue to exist today hedge fund managers who deliver high levels of alpha with clearly superior consistency ( Jagannathan et al 2010, Ammann et al 2010.…”
Section: Introductionmentioning
confidence: 99%